Lagrange linear equation
"(y^2+z^2-x^2 )p+2xyq+2zx=0\\\\\n(y^2 + z^2 - x^2)p + 2xyq =- 2zx"
from general form,
"Pp +Qq =R"
"P = y^2 + z^2 -x^2\\\\\nQ = 2xy\\\\\nR =-2zx"
From the auxiliary equation,
"\\dfrac{dx}{P}= \\dfrac{dy}{Q}= \\dfrac{dz}{R}"
"\\dfrac{dx}{y^2 +z^2 -x^2}= \\dfrac{dy}{2xy}= \\dfrac{dz}{-2zx} \\quad------(i)"
Taking the last 2 ratios
"\\dfrac{dy}{2xy}= \\dfrac{dz}{-2zx}"
"\\dfrac{dy}{y}= -\\dfrac{dz}{z}"
Integrating;
"\\log y = -(\\log z) + \\log c_1\\\\\n\\log y = -\\log z + \\log c_1\\\\\n\\log y +\\log z = \\log c_1\\\\\n\\log yz =\\log c_1"
"yz = c_1"
"c_1 = yz \\quad------(ii)"
Taking the first 2 ratios
"\\dfrac{dx}{y^2 +z^2 -x^2}= \\dfrac{dy}{2xy}"
but,
"c_1 = yz\\\\\n\\therefore z= \\dfrac{c_1}{y}"
substituting the value of z into the first 2 ratios,
we have,
"\\dfrac{dx}{y^2 +(\\frac{c_1}{y})^2 -x^2}= \\dfrac{dy}{2xy}"
"2xy\\, dx = (y^2 +(\\dfrac{c_1}{y})^2 -x^2)dy"
"2xy\\, dx - (y^2 +(\\dfrac{c_1}{y})^2 -x^2)dy = 0"
"2xy\\, dx - (y^2 +\\dfrac{c_1^2}{y^2}-x^2)dy = 0 \\quad------(iii)"
Integrating equation (iii)
"\\large \\int2xy\\, dx - \\int(y^2 +\\dfrac{c_1^2}{y^2}-x^2)dy = 0"
"\\large x^2y-\\dfrac{y^3}{3}+\\dfrac{c_1^2}{y} = c_2"
but, "c_1 = yz"
"\\therefore\\large x^2y-\\dfrac{y^3}{3}+yz^2 = c_2 \\quad------(iv)"
"\\therefore" the general solution is;
"\\large f(yz,\\,\\, x^2y- \\dfrac{y^3}{3} +yz^2) = 0"
Comments
Leave a comment